Cost-effectiveness of new pneumococcal conjugate vaccines in Turkey: a decision analytical model - (:unkn) unknown (BMC, 2012)
Background: Streptococcus pneumoniae infections, which place a considerable burden on healthcare resources, can be reduced in a cost-effective manner using a 7-valent pneumococcal conjugate vaccine (PCV-7). We compare the cost effectiveness of a 13-valent PCV (PCV-13) and a 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) with that of PCV-7 in Turkey. Methods: A cost-utility analysis was conducted and a decision analytical model was used to estimate the proportion of the Turkish population <10 years old that would experience 10 mutually exclusive outcomes over the course of 1 year from a perspective of a healthcare system. Model outcomes were adjusted according to the population demographics and region-specific serotype distribution in Turkey. Health outcomes and direct healthcare costs were simulated for PCV-7, PCV-13 and PHiD-CV. Results: PCV-13 and PHiD-CV are projected to have a substantial impact on pneumococcal disease in Turkey versus PCV-7, with 2,223 and 3,156 quality-adjusted life years (QALYs) and 2,146 and 2,081 life years, respectively, being saved under a 3+1 schedule. Projections of direct medical costs showed that a PHiD-CV vaccination programme would provide the greatest cost savings, offering additional savings of US$11,718,813 versus PCV-7 and US $8,235,010 versus PCV-13. Probabilistic sensitivity analysis showed that PHiD-CV dominated PCV-13 in terms of QALYs gained and cost savings in 58.3% of simulations. Conclusion: Under the modeled conditions, PHiD-CV would provide the most cost-effective intervention for reducing pneumococcal disease in Turkish children.
Keywords: NONTYPABLE HAEMOPHILUS-INFLUENZAE; ACUTE OTITIS-MEDIA; STREPTOCOCCUS-PNEUMONIAE; ANTIMICROBIAL RESISTANCE; BACTERIAL-MENINGITIS; ECONOMIC-EVALUATION; UNITED-STATES; PROTEIN-D; DISEASE; VACCINATION